Kazimierz Twardowski’s educational philosophy from the analytical perspective - Goncharenko, Olga (Hybris, 2017)
The reflection on philosophical foundations of pedagogy is characteristic feature of the analytical tradition in philosophy. The creative work of Kazimierz Twardowski, famous polish philosopher, is an integral part of this tradition. His papers together form the analytical project, which lay the ground for the formation of a particular style of philosiphizing in pedagogical dimension. These features are most clearly manifested in problematizing the relation between philosophy and pedagogy, in the analysis of pedagogical concepts, in the critic of irrationalism in pedagogy, in the coordination with scientific criticism in pedagogy.